Percutaneous high-frequency selective rhizotomy in the trigeminal neuralgia therapy in multiple sclerosis - V. M. Tyurnikov; A. V. Peresedova; A. O. Gushcha; I. A. Zavalishin (Нервно-мышечные болезни, 2015)
Trigeminal neuralgia is a rare symptom of multiple sclerosis affecting the disability. Multiple sclerosis related trigeminal neuralgia has been attributed to a demyelinating lesion in the pons. When the adequate pain drug-relieve therapy is not possible or when the patient becomes refractory to the treatment or can not continue pharmacological treatment because of the side effects, surgical intervention, including percutaneous radiofrequency rhizotomy is being discussed. Literature review and the data upon the efficiency and safety of this neurosurgical treatment in 16 patients with multiple sclerosis have been analyzed. Percutaneous radiofrequency rhizotomy has been proved to be a safe, reproducible and effective method of the symptomatic surgical treatment of trigeminal neuralgia in patients with multiple sclerosis in cases of the intolerance/inefficiency of the pharmacological therapy.